Stem Volume Allometric Equation of Acacia auriculiformis A. Cunn. Ex benth : Applicability of Digital Photography with Image Analysis as a Non-Destructive Approach - Farhana, Tasmia; Rafikul Islam, Md.; Hasan, Tamjid; Salim Azad, Md.; Mollick, Abdus Subhan; Khan, Nabiul Islam (Indian Forester, 2023)
Accurate estimate of stem volume is crucial to forest management. In this study, we developed allometric equations of stem volume of Acacia auriculiformis after destructive harvesting of 48 individual trees. We also took digital photographs of each sample tree just before destructive harvesting from the felling operations of Bangladesh Forest Department in short rotation (10-15 years) plantations. The aim of this study was to know the accuracy of the results obtained through image analysis in comparison with true values and to develop the best stem volume regression model of this species. The best-fit stem volume equation performed well when fitted against a set of different samples collected for field validation. There was a strong linear relationship between 'image stem volume' to 'true stem volume' (R2 = 0.959) suggesting the applicability of the digital photography method to derive stem volume allometric equations. The findings of this study may be potentially used for obtaining stem volume allometric equations on other precious species, where destructive harvest is not permitted. The results of this study have implications on estimation of tree level biomass and carbon stocks of forests.